The city : a novel - Koontz, Dean R. (Dean Ray), 1945- (New York : Bantam Books, 2014)
There are millions of stories in the city--some magical, some tragic, others terror-filled or triumphant. Young Jonah Kirk's story is all of those.
Keywords: Musicians -- Fiction; City and town life -- Fiction; Bildungsromans